A bit of statistics Get your fruit trees growing - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Fresh tropical fruits (excluding bananas) are still winning places on world markets. While total fresh fruit production has risen by 4% annually since 1997, some exports of diverse fruits have grown by more than 10% annually. The bulk of these...